Mitigasi Bencana Banjir di Desa Buluhcina Melalui Edukasi Sampah dan Pencemaran Lingkungan Kepada Siswa SDN 001 Buluhcina - Marbun, Afifah Marwa; Simangunsong, Sanni H; S, Sri Ariyani; Ambarita, Kevin Lastua Febrian; Damayanti, Amanda Riska; Rafsanjani, Fatimah; 'Ariq, Yusron; Tambunan, Reinward Immanuel; Putri, Marcela Hanindya; Mikeceal, Fernando (Riau Journal of Empowerment, 2024)
Flooding is a natural disaster that often occurs in Buluhcina Village. This disaster resulted in many multi-sectoral damages, ranging from health, economic and infrastructure problems. Therefore, it is necessary to carry out educational activities to increase knowledge, stimulate changes in attitudes, and direct people's behavior towards waste, pollution and environmental conservation. The educational activities carried out are focused on elementary school students who are often not involved in flood disaster mitigation efforts in Buluhcina Village.